STUDI LITERATUR KESEJAHTERAAN RUMAH TANGGA USAHA BUDIDAYA IKAN NILA DI KABUPATEN BENGKULU UTARA) - Fikri Islami; Yusnida Yusnida (Universitas Bengkulu, 2019)
This study aims to determine the characteristics of tilapia farmers in Sido Luhur Village, determine the level of income and sources of income of tilapia cultivator households, and determine the level of welfare of tilapia cultivator households. The method used in this study is descriptive qualitative, which is the characteristics of tilapia fishers, namely age, number of dependents, education level, business experience, pool area, and labor needed. To measure the level of welfare of tilapia cultivator households using measurements from the Central Agency for household welfare criteria based on BKKBN. The results of measurements of the level of well-being in the community of Sido Luhur Village, Padang Jaya Subdistrict, North Bengkulu Regency can be said to be prosperous, this is because tilapia farmers in general have met the criteria according to BKKBN indicators, because most of them have been able to fulfill their basic daily needs, as many as 33 respondents, which are in the third prosperous stratum, and according to research there are more tilapia farmers who are in the pre-prosperous category.Keywords: Hight of Welfare, Income